RAS as Supporting Actor in Breast Cancer - Galiè, Mirco (Frontiers in Oncology, 2019)
Oncogenic activation of Ras isoforms leads tumor initiation and progression in many types of cancers and is gaining increasing interest as target for novel therapeutic strategies. In sharp contrast with other types of cancer, the importance of RAS in breast tumorigenesis have been undermined by the low frequency of its oncogenic mutation in human breast tumors. Nevertheless, a wealth of studies over the last years have revealed how the engagement of Ras function might be mandatory downstream varied oncogenic alterations for the progression, metastatisation and therapy resistance in breast cancers. We review herein the major studies over the last three decades which have explored the controversial role of Ras proteins and their mutation status in breast tumorigenesis and have contributed to reveal their role as supporting actors, instead of as primary cause, in breast cancer.